Perlindungan Hak-Hak Anak pada Santri: Studi pada Pondok Pesantren Darul ‘Ulum Jombang - Fathurrahman, Ali Masykur; Kusdarini, Eny; Hanum, Fathikah Fauziah; Febiantoni, Fungki; Aziz, Sulthon Abdul (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
This community service aims to carry out socialization and training in understanding the Protection of Children's Rights at the Darul 'Ulum Jombang Islamic Boarding School Students. This community service is an activity that is carried out using lecture, question and answer, and discussion methods in a series of socialization activities. While the training methods carried out are in the form of training and practical activities in increasing the understanding and protection of children's rights. Activity evaluation is carried out by measuring how well the target group knows and understands how to prevent sexual violence at Darul 'Ulum Jombang Islamic Boarding School. The result of this community service activity is increased insight in the form of knowledge and understanding of students and stakeholders at the Darul 'Ulum Jombang Islamic boarding school regarding the protection of children's rights, especially against violence in Islamic boarding schools. Through this training, the students and stakeholders helped increase their insight in terms of preventing violence in the Darul 'Ulum Jombang Islamic Boarding School environment.